2010
DOI: 10.1086/654897
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Patterns Associated with the 1918 Influenza Pandemic in Mexico: Evidence for a Spring Herald Wave and Lack of Preexisting Immunity in Older Populations

Abstract: Background While the mortality burden of the devastating 1918 influenza pandemic has been carefully quantified in the US, Japan, and European countries, little is known about the pandemic experience elsewhere. Here, we compiled extensive archival records to quantify the pandemic mortality patterns in two Mexican cities, Mexico City and Toluca. Methods We applied seasonal excess mortality models to age-specific respiratory mortality rates for 1915–1920 and quantified the reproduction number from daily data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
112
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 43 publications
13
112
1
1
Order By: Relevance
“…Further reports from the United States and Europe have shown that influenza-related deaths among seniors ( > 50 years of age) were significantly reduced during the lethal 1918–19 pandemic wave relative to baseline periods. In contrast, this protective effect for seniors did not apply to Mexico, Colombia, and remote island populations, probably because of differences in prior immunity between regions ( 6 , 13 ). In addition, large geographic variations in mortality rates from the pandemic have been documented ( 14 16 ).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Further reports from the United States and Europe have shown that influenza-related deaths among seniors ( > 50 years of age) were significantly reduced during the lethal 1918–19 pandemic wave relative to baseline periods. In contrast, this protective effect for seniors did not apply to Mexico, Colombia, and remote island populations, probably because of differences in prior immunity between regions ( 6 , 13 ). In addition, large geographic variations in mortality rates from the pandemic have been documented ( 14 16 ).…”
mentioning
confidence: 81%
“…Our understanding of the epidemiologic patterns of this pandemic has improved over the past decade as a result of intensive efforts to locate, digitize, and analyze archival disease records ( 3 ). In particular, studies focusing on the United States ( 4 , 5 ), Mexico ( 6 ), Colombia ( 7 ), Brazil ( 8 ), and Peru ( 9 ) have shed light on geographic variation in the patterns of timing, intensity, and patient age during successive pandemic waves across the Americas. Yet there have been no reports from temperate locales of South America; this gap prevents a complete understanding of the epidemiology of the pandemic throughout the continent and across different climatic zones.…”
mentioning
confidence: 99%
“…The epidemiology of the three influenza pandemics of the 20th century (1918 [H1N1], 1957 [H2N2], and 1968 [H3N2]) has been studied intensively, particularly the variation in mortality and transmissibility among countries and cities and between successive waves (1,6,18). However, the viral gene sequence data acquired from these past pandemics has been insufficient to precisely reveal epidemiological patterns and dynamics, especially at the level of individual cities.…”
mentioning
confidence: 99%
“…In 2006, a seminal study revealed more than 30-fold variation in 1918 pandemic excess mortality rates across a sample of 20 countries, with socioeconomic factors explaining a significant fraction of the observed variation (2). In Latin America, pandemic excess mortality rates varied from 0.4 to 2.9% in national and province-level data, a greater than sevenfold variation (4,8,9). In contrast, United States and European populations fared relatively well during the pandemic, despite intense disruption at the end of World War I (excess mortality rates of 0.5-1.1%) (3,5).…”
mentioning
confidence: 99%